2018
DOI: 10.1016/j.nima.2018.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation study of a fully monolithic HV-CMOS pixel sensor design in AMS 180 nm

Abstract: High-Voltage Monolithic Active Pixel Sensors (HV-MAPS) based on a 180 nm HV-CMOS process have been proposed to realize thin, fast and highly integrated pixel sensors. The MuPix7 prototype, fabricated in the commercial AMS H18 process, features a fully integrated on-chip readout, i.e. hit-digitization, zero suppression and data serialization. MuPix7 is the first fully monolithic HV-CMOS pixel sensor that has been tested for the use in high irradiation environments like HL-LHC. We present results from laboratory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, the depletion depth of ≈ 30 µm allows to remove the remaining substrate and thereby thinning of the sensors to 50 µm thickness. Using commercially available processes, the MuPix chips [3][4][5][6][7] have been developed, culminating in the first large scale HVMAPS sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the depletion depth of ≈ 30 µm allows to remove the remaining substrate and thereby thinning of the sensors to 50 µm thickness. Using commercially available processes, the MuPix chips [3][4][5][6][7] have been developed, culminating in the first large scale HVMAPS sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Even higher radiation tolerances were recently reported for sensors relying on large ll factor diodes or modied CMOS processes (see e.g. [110,111]), which are however not subject of this work.…”
Section: Integrated Displacement Damage Caused By Heavy Ionsmentioning
confidence: 81%
“…The radiation hardness of the AMS H18 process has been investigated in previous works [11,12] including an electrical characterisation of irradiated ATLASPix1 prototypes [13]. Single hit efficiencies for a fully monolithic HV-MAPS 1 irradiated with protons and neutrons were reported first for the MuPix7 predecessor [14] which has no radiation hard design. These performance studies have been repeated for the ATLASPix1_Simple prototype and first results were reported in [5].…”
Section: Pos(vertex2019)024mentioning
confidence: 99%